PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERATING - Gustiana, Kharisma Yogi; Safriliana, Retna; Subiyantoro, Edi (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to examine the effect of firm size, leverage, and profitability on tax avoidance, with independent commissioners as a moderating variable in financial sector companies listed on the Indonesia Stock Exchange for the period 2021–2023. The research method used is a quantitative approach with purposive sampling, resulting in 98 companies or 294 observations. Data were analyzed using Moderated Regression Analysis (MRA). The results show that firm size and profitability have a negative effect on tax avoidance, while leverage has a positive effect. Independent commissioners are proven to moderate the effect of firm size and leverage on tax avoidance, but not the effect of profitability. This study contributes to strengthening corporate governance in minimizing tax avoidance practices in the financial sector.Keywords:Tax Avoidance, Firm Size, Leverage, Profitability, Independent Commisioners